Bis(imidazolium)‐1, 3‐diphosphete‐diide: A Building Block for FeC2P2 Complexes and Clusters. (11th July 2022) - Scharnhölz, Moritz Theodor; Coburger, Peter; Gravogl, Lisa; Klose, Daniel; Gamboa‐Carballo, Juan José; Le Corre, Grégoire; Bösken, Jonas; Schweinzer, Clara; Thöny, Debora; Li, Zhongshu; Meyer, Karsten; Grützmacher, Hansjörg
Abstract: Reaction of the 6π‐electron aromatic four‐membered heterocycle (IPr)2 C2 P2 (1 ) (IPr=1, 3‐bis(2, 6‐diisopropylphenyl)‐1, 3‐dihydro‐2 H ‐imidazol‐2‐ylidene) with [Fe2 CO9 ] gives the neutral iron tricarbonyl complex [Fe(CO)3 ‐η 3 ‐(IPr)2 C2 P2 ] (2 ). Oxidation with two equivalents of the ferrocenium salt, [Fe(Cp)2 ](BArF24 ), affords the dicationic tricarbonyl complex [Fe(CO)3 ‐η 4 ‐(IPr)2 C2 P2 ](BArF24 )2 (4 ). The one‐electron oxidation proceeds under concomitant loss of one CO ligand to give the paramagnetic dicarbonyl radical cation complex [Fe(CO)2 ‐η 4 ‐(IPr)2 C2 P2 ](BArF24 ) (5 ). Reduction of 5 allows the preparation of the neutral dicarbonyl complex [Fe(CO)2 ‐η 4 ‐(IPr)2 C2 P2 ] (6 ). An analysis by various spectroscopic techniques ( 57 Fe Mössbauer, EPR) combined with DFT calculations gives insight into differences of the electronic structure within the members of this unique series of iron carbonyl complexes, which can be either described as electron precise or Wade–Mingos clusters. Abstract : Bis‐imidazolium‐diphosphete‐diide, (IPr)2 C2 P2, acts as an electronically remarkably flexible ligand to iron carbonyl fragments, giving access to complexes of the general formula [Fe(CO) x (IPr)2 C2 P2 ] n + ( x =2, 3; n =0, +1, +2). Redox events involve either the metal ion or C2 P2 ligand, as demonstrated by EPR, Mössbauer and computational analyses and characterize (IPr)2 C2 P2 as a redox active ligand.